Peningkatan Wawasan Orang Tua dalam Teknik Dongeng untuk Mengenalkan Pendidikan Karakter Anak Usia Dini - Tiara Widyaiswara; Dian Luthfiyati; Riya Risqi Setyaningrum; Moh Nurman (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2024)
This dedication aims to improve the ability of parents in storytelling techniques to their early age children, this form of dedication is an effort to introduce character education and instill moral values ​​in children through storytelling. This training activity is carried out in the form of an interactive workshop between speakers, parents, and teachers at Surya Baru Kindergarten and Melati Early Kindergarten in Plosogeneng district, Plosowahyu Village, Lamongan. The dedication was carried out on August 21, 2024. The methods implemented in this dedication are 1) conducting a survey of the dedication location, 2) analyzing problems, 3) planning a dedication concept, 4) training activities in the form of interactive workshops, 5) monitoring and evaluating dedication activities. The results obtained from this dedication are that parents can apply good storytelling techniques to their children. Thus, it is a step to instill character education in children from an early age which has a long-term impact as human beings who are virtuous. With this dedication, parents gain insight into the importance of fairy tales so that they can play a more active role in children's character education.